2021
DOI: 10.1002/mbo3.1173
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of Lactobacillus cell‐free supernatants against multidrug‐resistant urogenital pathogens

Abstract: The healthy vaginal microbiota is dominated by Lactobacillus spp., which provide an important critical line of defense against pathogens, as well as giving beneficial effects to the host. We characterized L. gasseri 1A‐TV, L. fermentum 18A‐TV, and L. crispatus 35A‐TV, from the vaginal microbiota of healthy premenopausal women, for their potential probiotic activities. The antimicrobial effects of the 3 strains and their combination against clinical urogenital bacteria were evaluated together with the activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 56 publications
2
52
0
1
Order By: Relevance
“…Supernatants were collected and filter-sterilized with a 0.22 μm filter (Millipore, USA). The antimicrobial activity of CFS was evaluated initially according to the effect of CFS on the viability of the pathogenic bacteria [ 44 ] and appropriate modifications. Briefly, overnight pathogenic cultures were sub-cultured in TSB at 37℃ to logarithmic phase.…”
Section: Methodsmentioning
confidence: 99%
“…Supernatants were collected and filter-sterilized with a 0.22 μm filter (Millipore, USA). The antimicrobial activity of CFS was evaluated initially according to the effect of CFS on the viability of the pathogenic bacteria [ 44 ] and appropriate modifications. Briefly, overnight pathogenic cultures were sub-cultured in TSB at 37℃ to logarithmic phase.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we showed that, like other Lactobacillus species (Kang et al, 2018;Jang et al, 2019;Scillato et al, 2021), L. johnsonii displays anticandidal properties, reducing C. albicans growth and ability to transition into hyphae and establish biofilms on abiotic surfaces. We found that the MT4 strain shows strong dose-dependent anticandidal activity, particularly in the biofilm growth phase.…”
Section: Discussionmentioning
confidence: 84%
“…L. jensenii showed an individual probiotic effect against AV. Although the protective effect of L. gasseri against BV is well known ( Scillato et al., 2021 ), its individual effect is overlapped when other Lactobacillus species are present in the same cluster, in particular L. iners and L. crispatus . However, the present study has several limitations, such as the absence of longitudinal analysis between vaginal infections and sociodemographic/behavioral variables or lactobacilli, only one vaginal sample was collected of each volunteer, and the lack of quantitative data.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal microbiota balances the health state of women through its ability to prevent potential dysbiosis or infections ( Pacha-Herrera et al., 2020 ; Joseph et al., 2021 ). Healthy women usually show a diversity of anaerobic and aerobic microorganisms in the vaginal epithelium ( Borges et al., 2013 ), in which lactobacilli are the dominant species and act as a protective barrier to prevent pathogenic colonization ( Di Cerbo et al., 2016 ; Scillato et al., 2021 ). However, the vaginal colonization by different lactobacilli species depends also on their ability to produce antimicrobial compounds, such as hydrogen peroxide, lactic acid, and bacteriocin-like substances ( Borges et al., 2013 ; Castillo-Juárez et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%